Nivel de logro de las competencias comunicativas en los estudiantes del quinto grado de secundaria de la I.R. N° 601582 Agustín Rivas Vásquez, distrito de Fernando Lores 2021 - Lopez Marin, Evelin Azucena (2023)
The objective of the research was: To determine the level of achievement of communicative skills in fifth grade high school students of the I.E N° 601582 Agustín Rivas Vásquez, district of Fernando Lores-2021. The type of research is quantitative, descriptive and has a simple descriptive design. The population and sample consisted of 47 students in the fifth year of high school. The data collection instruments were an observation sheet to evaluate oral communication, a questionnaire for text comprehension and a performance test for text production. The results show that the level of achievement of communicative competences is in process obtaining a (82.98%) and that the competence communicates orally in his mother tongue is also in process with him (68.09) while in the competence he reads various types of text in their mother tongue we have (91.49%), being in process level, as for the competence writes various types of texts in their mother tongue, we have a (72.34%) that is in process. It was concluded that the level of communication skills is acceptable for the current educational system in rural areas.